Library Care: Strategi Optimalisasi Koleksi dan Administrasi Perpustakaan SDN 2 Poncokusumo - Fatihah, Zinniya; Hidayat, Wildan; Nazihah, Ikrimah Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Community service activities carried out by the 94 KKM group of UIN Maulana Malik Ibrahim Malang at SDN 2 Poncokusumo, Malang Regency, East Java, for the 2023/2024 KKM period aim to optimize the school library. Every school certainly has a library to support the learning and teaching process. Library optimization aims to maximize the existence of the school library so that it can be utilized properly and improve the quality of the library. The series of activities carried out included library surveys, collection data collection, labeling books, arranging books on shelves, creating library administration, and creating information boards. Optimization in the SDN 2 Poncokusumo library focuses more on book labeling activities. Through collaboration between students and the school, it is hoped that the SDN 2 Poncokusumo library can be better at supporting the teaching and learning process and developing students' interest in reading.